2020
DOI: 10.3389/fnhum.2020.00197
|View full text |Cite
|
Sign up to set email alerts
|

Using Functional Near-Infrared Spectroscopy to Assess Brain Activation Evoked by Guilt and Shame

Abstract: Functional near-infrared spectroscopy (fNIRS) is a promising brain imaging modality for studying the neural substrates of moral emotions. However, the feasibility of using fNIRS to measure moral emotions has not been established. In the present study, we used fNIRS to detect the brain activation evoked by two typical moral emotions-guilt and shame. We presented the participants with guilt and shame context to evoke emotional responses and measured the brain activity by using fNIRS. The univariate general linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Duan et al found that shame and embarrassment resulted in increased activity in the inferior temporal, anterior temporal regions, and the parietal gyrus [ 84 ], similar to those found in guilt [ 79 , 81 ]. Tapping into social cognition [ 85 ], it has also been found that witnessing the self-embarrassment of others activates the right middle temporal gyrus (rMTG) and the rTPJ [ 86 ].…”
Section: Shame and Embarrassmentmentioning
confidence: 94%
“…Duan et al found that shame and embarrassment resulted in increased activity in the inferior temporal, anterior temporal regions, and the parietal gyrus [ 84 ], similar to those found in guilt [ 79 , 81 ]. Tapping into social cognition [ 85 ], it has also been found that witnessing the self-embarrassment of others activates the right middle temporal gyrus (rMTG) and the rTPJ [ 86 ].…”
Section: Shame and Embarrassmentmentioning
confidence: 94%
“…Moreover, here we found that the participants’ communal concern (gratitude and guilt) also increased as a function of TPJ activation in different conditions. 73 , 74 For example, TPJ has been shown to be correlated with gratitude. 75 The TPJ is also activated in studies involving the guilt condition.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the use of VR to elicit aggression will require specific safety protocols to minimize ethical and safety concerns (159). Alternative devices that are less sensitive to motion, such as electroencephalogram (EEG) or functional near-infrared spectroscopy (fNIRS) could also be used (160,161).…”
Section: Limitationsmentioning
confidence: 99%